On stochastic aspects of impact modeling of the innovation incentive system and business internationalization - Grilo, L. M. (2024)
Funding Information: This work is funded by national funds through the FCT - Fundação para a Ciência e a Tecnologia, I.P., under the scope of the projects UIDB/00297/2020 and UIDP/00297/2020 (Center for Mathematics and Applications). Publisher Copyright: © 2023 The Author(s). Published with license by Taylor & Francis Group, LLC.